2018
DOI: 10.1002/pds.4579
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the possible association of anti‐TNF use with new malignancies: A neglected methodological consideration

Abstract: Purpose Whether anti‐TNF agents increase, malignancy risk remains debated. The potential problems with comparing the number of observed malignancies in anti‐TNF treated cohorts to number of expected malignancies in national cancer registries could have been an important issue. National registries give expected number of malignancies per organ involved regardless of if this is a secondary or a higher malignancy while anti‐TNF agents are not or are sparingly used in patients with an existing or history of a mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(183 reference statements)
0
2
0
Order By: Relevance
“…However, uncertainty remains because of the fact that even recent studies (prospective trials and population-based trials) failed to confirm a strict correlation with increased risk for malignancies [1,7]. Another confounding factor is defined by increased disease activity that strongly correlates with lymphoma risk [15] especially in case of RA. A group of Korean researchers tried to estimate the incidence of malignancy in early RA patients and to evaluate the relative risk of malignancy by using the Korean National Claims Database comprising a total of 14,081 identified patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncertainty remains because of the fact that even recent studies (prospective trials and population-based trials) failed to confirm a strict correlation with increased risk for malignancies [1,7]. Another confounding factor is defined by increased disease activity that strongly correlates with lymphoma risk [15] especially in case of RA. A group of Korean researchers tried to estimate the incidence of malignancy in early RA patients and to evaluate the relative risk of malignancy by using the Korean National Claims Database comprising a total of 14,081 identified patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observational studies comparing the observed cancer incidence in an RA cohort with that reported in a national cancer registry, it has also been stated that treatment with a biologic agent does not appreciably increase the incidence of neoplasms among RA patients (5,6). However, as we recently pointed out, there has been a common methodologic error in such comparisons (7). There are 3 important considerations.…”
Section: To the Editormentioning
confidence: 99%